PENERAPAN MODEL DISCOVERY LEARNING BERBANTUAN GOOGLE CLASSROOM UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Puspananda Damayanti; Siti Nurul Hidayati (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2022)
This research aimed to describe the implementation of learning, students’ responses, and learning outcomes in aspects of attitude and knowledge using the discovery learning model assisted by Google Classroom. This research used a pre-experimental with one group pretest posttest design. Samples in this research were 17 students of VII-A class in SMP NU Bahrul Ulum Gresik in the Academic Year 2021/2022. The data were collected using observations, questionnaires, and tests in the form of learning implementation observation sheets, student response questionnaires, attitude assessment sheets, and test assessment sheets as the instruments. The results showed that: (1) the implementation of learning with a discovery learning model assisted by Google Classroom at each stage in three meetings got a very good category; (2) the implementation of discovery model assisted by Google Classroom got positive responses from students with a very good category; (3) learning outcome of social attitudes aspects which include cooperative attitudes, curiosity attitudes, and attitudes of responsibility were declared complete with good and very good predicates; (4) learning outcome in the knowledge aspect increased as evidenced by the average value of N-gain in high category.